English as a Medium for Accessing the Modern World - Harno Diyansyah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
English has developed into an international language that plays a vital role in various sectors of life, including education, technology, business, and global communication. This study aims to analyze the role of English as a language of introduction to the modern world and the challenges of English language acquisition in Indonesia. The method used is a literature review with a descriptive qualitative approach. The analysis shows that English is a gateway to globalization, but English language acquisition in Indonesia still faces obstacles such as limited language environments, less communicative learning methods, and disparities in access to education. This article recommends English learning strategies based on digital technology, a communicative approach, and integration of local culture to make learning more effective and relevant.